Răspuns :
A=l²√3/4
36√3=l²√3/4
36√3 *4=l²√3
l²=36*4
l=6*2=12
P=3*l=3*12=36
H=l√3/2=6√3
R=l/√3=6/√3
r=l√3/6=√3
Fie A, B si C laturile triunghiului echilateral
Fie AM inaltime si med in ΔABC
Arie=36√3
[tex] \frac{l ^{2} \sqrt{3} }{4} [/tex]=36
[tex] l^{2} \sqrt{3} =144 \sqrt{3} [/tex]
[tex] l^{2} =144[/tex] ⇒ l=12
P=l·3=12·3=36
TP: ⇒[tex] AB^{2} = BM^{2} + AM^{2} 144=36+AM^{2} AM^{2}=108[/tex] ⇒ AM=[tex]6 \sqrt{3} [/tex]
r=[tex] \frac{AM}{3}= \frac{6 \sqrt{3} }{3} =2 \sqrt{3} [/tex]
R=r·2=[tex]2 \sqrt{3} [/tex]·2=[tex]4 \sqrt{3} [/tex]
Fie AM inaltime si med in ΔABC
Arie=36√3
[tex] \frac{l ^{2} \sqrt{3} }{4} [/tex]=36
[tex] l^{2} \sqrt{3} =144 \sqrt{3} [/tex]
[tex] l^{2} =144[/tex] ⇒ l=12
P=l·3=12·3=36
TP: ⇒[tex] AB^{2} = BM^{2} + AM^{2} 144=36+AM^{2} AM^{2}=108[/tex] ⇒ AM=[tex]6 \sqrt{3} [/tex]
r=[tex] \frac{AM}{3}= \frac{6 \sqrt{3} }{3} =2 \sqrt{3} [/tex]
R=r·2=[tex]2 \sqrt{3} [/tex]·2=[tex]4 \sqrt{3} [/tex]